PENGARUH PENDELEGASIAN WEWENANG DAN TANGGUNG JAWAB TERHADAP EFEKTIVITAS KERJA PEGAWAI PADA DINAS KESEHATAN PROVINSI SUMATERA UTARA - Ekty Lovenda; Adelina Lubis; Syahriandy Syahriandy (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
The study aims to determine “The effect of Delegation of authority and Responsibility on the work effectiveness of employees at the North Sumatera Provincial Health Office”.The type of data in this study is Associative,namely research that has the question of the relationship between two independent variables.The population in this study were 296 permanent employees of  the North Sumatera Provincial Health Office.Based on the calculation of Slovin formula,the number of samples studied was 75 respondents.The sampling technique in this study was conducted by random sampling technique with error 0,10.The obtain data in the preparation oh this essay,the author uses instruments: Documentation studies,Intervuews and quesionnaires.Based on the results of the t test the delegation of authority variables get the value of  t _count of 2.198 t_table 1,933 and a significant value of 0,0310,05 and the Resposibility variable obtained t_count of 10,072t_table 1,933 and a significant value 0f 0,0000,05.The results of this study indicate that partially,Delegation of authority and Resposibility on the work of effectiveness of employees at the North Sumatera Provincial Health Office.The work Effectiveness is jointly influenced by delegation of authority and responsibility can be seen in the Adjusted R square value of 609 or 60,9% against the dependent variable which is the work Effectiveness simultaneously has a significant effect,while the remaining 39.1% is influenced by other variables not discussed tn the study.